VD_FINDINFO HC / 2013 / 510 vom 8. August 2013 - VD Tribunal cantonal (2013)
DROIT DE GARDE, PROTECTION DE L'UNION CONJUGALE, LOGEMENT DE LA FAMILLE | 176 al. 1 CC, 176 al. 3 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)